AN EMPOWERMENT OF VILLAGE APPARATUS IN ECOTOURISM-BASED MANGROVE MANAGEMENT IN TAPAK KUDA VILLAGE, TANJUNG PURA DISTRICT, LANGKAT DISTRICT - Farid Aulia; Yeni Absah (Sean Institute, 2023)
Ecotourism-based mangrove management in Tapak Kuda Village through empowering village officials is still hampered in various aspects. These aspects include: the low ability of village officials to reduce the increasingly massive rate of mangrove forest encroachment, the low knowledge of village officials regarding the development of ecotourism in managing mangrove forests as an effort to improve the economy of village communities, the low level of empowerment of village officials in organizing partnerships and managing collective businesses based on ecotourism, including: services that prioritize comfort, friendliness, cleanliness, a variety of halal food with a delicious and affordable taste, availability of adequate infrastructure, maintaining environmental cleanliness from the generation of organic and non-organic waste. organic. To achieve this goal, the method used in this activity is: Ecotourism Development Socialization and Training. Participatory Organizing, Monitoring and Evaluation. The achievement of this regular mono-year partnership is that the partner group (village apparatus) is able to become a community driver in managing mangroves sustainably and sustainably through the development of ecotourism which is able to improve community welfare.